Virtual Literary Communities: Fostering the reading of English language books by Brazilian readers (Research, Society and Development, 2025)
This article analyzes how digital literary communities Booktwitter (X), Bookgram (Instagram) and Skoob contribute to the dissemination of English-language books among Brazilian readers on social networks. Based on a qualitative and bibliographic approach using public posts as illustrations of online trends, it was observed that these platforms are environments that illustrate participatory culture and collective intelligence (Jenkins, 2015), the social concept of literature (Candido, 2006; Botelho & Hoelz, 2016) and the dynamism of the reading activity (Pinto, 2015). The results indicate that while Booktwitter promotes textual debates and collective curatorship through real-time interactions, Bookgram emphasizes visual aesthetics, transforming books into objects of desire and identity performance, and Skoob combines both communities into quantitative data. It was concluded that the sharing of English-language books varies depending on the platform used and the member's reasons for that also diverge. Regardless of that, these communities offer a space that fosters inclusive and diverse literary debates, contributing to the ongoing evolution of literature.